Biofouling and scaling control of reverse osmosis membrane using one-step cleaning - potential of acidified nitrite solution as an agent - Filloux, Emmanuelle; Wang, Jingshi; Pidou, Marc; Gernjak, Wolfgang; Yuan, Zhiguo (Elsevier, 2015)
Biofouling is generally regarded as a major issue in reverse osmosis (RO) membrane ﬁltration. Two-step chemical cleanings with alkaline and acidic agents are typically applied to restore the treatment capacity. In this study, the feasibility of one-step cleaning using free nitrous acid (FNA) was investigated as a novel low cost cleaning agent. The FNA cleaning solution was prepared by acidiﬁcation of a sodium nitrite solution with hydrochloric acid. Seven fouled RO membranes collected from full-scale wastewater recycling and desalination plants were used to perform lab-scale cleaning trials. Membrane fouling characterisation revealed six of out of seven membranes were mainly bio-fouled, while one membrane was severely fouled by calcium carbonate. This study showed the feasibility of using FNA at pH 3.0 for biomass removal as well as for calcium carbonate scaling removal. The results from the lab-scale cleaning tests suggested that FNA can be used as a single cleaning agent for both biofouling and scaling removal. Cost analysis showed that FNA is a cost-effective solution for biofouling and scaling removal in RO ﬁltration applications.
Keywords: Biofouling; Free nitrous acid; Membrane cleaning; Reverse osmosis